2019
DOI: 10.1111/tri.13420
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation and Affordable Care Act Medicaid expansion in the era of lung allocation score – a retrospective study

Abstract: Summary This study evaluated the impact of Medicaid eligibility expansion (ME) on lung transplant (LT) listings and Medicaid coverage. Data on LT candidates aged 18–64 were obtained from the Scientific Registry of Transplant Recipients (N = 9153). The impact of ME was evaluated by comparing LT listings in 2011–2013 with listings in 2014–2016, as well as comparing states that had and had not adopted ME in 2014. LT listings increased by 7.7% nationally post‐ME. In ME states, LT listings increased by 15.2%, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…[9][10][11][12][13] Expansion has also led to increased utilization of preventative services, [14,15] more discretionary surgeries, [16] higher rates of early cancer diagnoses, [17] and improvements in all-cause mortality. [18] In addition to increasing the proportion of Medicaid patients on the kidney, lung, and heart transplant waitlists, [19][20][21] ACA Medicaid expansion has been associated with increased Medicaid use on the LT waitlist [22,23] and variable impacts based on race/ethnicity. [24] Recent studies have demonstrated an association between Medicaid expansion and improvements in nontransplantspecific liver disease-related mortality, particularly in states with lenient Medicaid coverage for direct-acting antivirals (which started becoming widely available as HCV treatment around the same time as when states started expanding Medicaid).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Expansion has also led to increased utilization of preventative services, [14,15] more discretionary surgeries, [16] higher rates of early cancer diagnoses, [17] and improvements in all-cause mortality. [18] In addition to increasing the proportion of Medicaid patients on the kidney, lung, and heart transplant waitlists, [19][20][21] ACA Medicaid expansion has been associated with increased Medicaid use on the LT waitlist [22,23] and variable impacts based on race/ethnicity. [24] Recent studies have demonstrated an association between Medicaid expansion and improvements in nontransplantspecific liver disease-related mortality, particularly in states with lenient Medicaid coverage for direct-acting antivirals (which started becoming widely available as HCV treatment around the same time as when states started expanding Medicaid).…”
Section: Introductionmentioning
confidence: 99%
“…Universal population coverage, however, is more broadly needed to ensure equitable care for all patients, including those with advanced lung disease. Notably, one analysis identified an association between the Affordable Care Act’s Medicaid expansion and the listing of Medicaid patients for lung transplantation ( 14 ).…”
mentioning
confidence: 99%
“…The perceived cost of care and possibility of lower reimbursement may influence perceptions regarding candidacy of Medicaid recipients and the attendant financial hurdles may further detract from successful wait‐listing, leaving limited options in the face of end‐stage lung disease. Obtaining coverage is often left to the discretion of individual state legislators to decide extent of Medicaid coverage for vulnerable populations, particularly females, non‐Caucasians and those living in rural states . The coverage varies by state.…”
mentioning
confidence: 99%